2013
DOI: 10.1088/0953-2048/26/10/105007
|View full text |Cite
|
Sign up to set email alerts
|

Magnetostrictive behaviors of type-II superconducting cylinders and rings with finite thickness

Abstract: This paper presents an investigation of the magnetostrictive behaviors of type-II superconducting cylinders and rings with finite thickness in the presence of a uniform applied field directed along the axis by means of the minimization of magnetic energy and the finite element method. The dependence of the magnetostriction and mechanical response upon the geometry of the superconductors is systematically studied in terms of Bean's critical state model with consideration of the demagnetizing effects. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…The compressive and tensile hoop stresses were, respectively, concentrated at the innermost peripheral edge of the infinite ring bulk during the ascending and descending stages of the PFM process, together with the compressive stress due to the thermal contraction by cooling. Huang et al investigated the magnetostriction of superconducting cylinders and rings with finite height by FEM [16], in which Bean's model and a uniform applied field using an infinite magnetizing solenoid coil were assumed. They concluded that the mechanical response of the finite height bulk is similar to that of an infinitely long bulk, but there is also a difference due to boundary and demagnetization effects.…”
Section: Introductionmentioning
confidence: 99%
“…The compressive and tensile hoop stresses were, respectively, concentrated at the innermost peripheral edge of the infinite ring bulk during the ascending and descending stages of the PFM process, together with the compressive stress due to the thermal contraction by cooling. Huang et al investigated the magnetostriction of superconducting cylinders and rings with finite height by FEM [16], in which Bean's model and a uniform applied field using an infinite magnetizing solenoid coil were assumed. They concluded that the mechanical response of the finite height bulk is similar to that of an infinitely long bulk, but there is also a difference due to boundary and demagnetization effects.…”
Section: Introductionmentioning
confidence: 99%
“…The composite film’s material parameters and device geometry changes are meaningful and achievable based on currently available published works [ 56 , 62 , 63 , 64 ]. As shown in Figure 5 a, the relationship between the AR and magnetic field is calculated when the saturation magnetostriction changes from 50 ppm to 170 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…The Material Properties of The WCR The magnetostrictive material is based on Fe-based soft ferromagnetic materials, and the parameters are reasonably selected based on the current works. The key material parameters used by the analytical model and FEM are given as follows [ 30 , 56 , 62 , 63 , 64 ]: The saturation magnetostriction ppm, the saturation magnetization , the effective magnetocrystalline anisotropy energy density KJ/m 3 , the in-plane easy-axis direction , the rotational deviation around the mean easy-axis angle , the energy density deviation around the mean easy-axis angle , and the static initial magnetic susceptibility . The AC voltage magnitude is V applied to the piezoelectric layer of R2, with the damping loss factor , Young’s modulus of the magnetostrictive layer GPa, Poisson’s ratio of the magnetostrictive layer , magnetostrictive material density kg/m 3 , the piezoelectric layer GPa, kg/m 3 , the substrate layer GPa, kg/m 3 .…”
Section: Appendix B1 the Geometric Parameters Of The Wcrmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, The mechanical behaviors of thin superconducting disk with a concentric hole and rectangular superconducting slab with a central rectangular hole were studied [16,17]. Then, more complex structures or critical state model are considered to predict the mechanical deformation and stability [18][19][20]. The stress distribution of an infinite hollow superconducting cylinder was studied analytically [21].…”
Section: Introductionmentioning
confidence: 99%